Gut Hormone Suppression Increases Food Intake After Esophagectomy With Gastric Conduit Reconstruction. Issue 5 (November 2015) - Elliott, Jessie A.; Jackson, Sabrina; King, Sinead; McHugh, Ruth; Docherty, Neil G.; Reynolds, John V.; le Roux, Carel W.
Abstract : Objectives: To characterize the gut hormone profile and determine the effect of satiety gut hormone blockade on food intake in disease-free postesophagectomy patients. Background: Improved oncologic outcomes for esophageal cancer have resulted in increased survivorship and a focus on health-related quality of life. Anorexia and early satiety are common, but putative causative factors, in particular the gut-brain hormonal axis, have not been systematically studied. Methods: In a double-blind, placebo-controlled, randomized crossover study, disease-free patients at least 1 year postresection and gastric conduit reconstruction received either 1 mL 0.9% saline or 1 mL (100 μg) octreotide acetate subcutaneously followed by a standardized ad libitum meal on each of two assessments. Fasting and postprandial plasma glucagon-like peptide 1 (GLP-1), peptide YY (PYY), and ghrelin immunoreactivity were measured. Gut hormone responses and calorie intake postsaline versus octreotide were compared between experimental and control groups. Results: Eighteen subjects [esophagectomy (ES), n = 10, 2.4 ± 0.75 years postresection; and unoperated control subjects, n = 8] were studied. ES demonstrated significant weight loss at 3, 6, 12, and 24 months postoperatively (all P  < 0.05). Ghrelin levels were similar ( P  = 0.58) for both groups, but postprandial GLP-1 and PYY responses were significantly ( P  < 0.001) greater among ES as compared with controls. After octreotide, ad libitum calorie intake increased among ES (1.5 ± 0.2 fold-change, P  = 0.02) but not controls (1.1 ± 0.1 fold-change, P  = 0.30). Conclusions: ES demonstrated an exaggerated postprandial satiety gut hormone response that was attenuated by octreotide, thus identifying a potential therapeutic target to modulate in the ES patient with early satiety. Abstract : Supplemental Digital Content is available in the text